1985
DOI: 10.1007/bf01411893
|View full text |Cite
|
Sign up to set email alerts
|

Disparity of measured gyromagnetic ratios of ground- and excited-band states in184W

Abstract: Gyromagnetic ratios of levels in the ground-band and of the 2 2 state in lS4W were measured by means of the transient magnetic field perturbed 7-ray angular distribution technique. The levels of interest were Coulomb excited by beams of 220-MeV SSNi and 63Cu ions. The results show the g-factor of the 2 2 state to be approximately half the effectively constant value found for the ground-band levels. This disparity is compared with those previously obtained for the corresponding states in 188-192Os and l*6W; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…4. While only the overall transition intensity was adjusted to fit the data for the 548-keV E2 transition, the mixing ratios were also varied to fit the correlations for the mixed were also in agreement with those measured and are similar to those published for la4W in [13]. A partial level scheme of 197Au which incorporates several firm spin assignments determined in our related study [20,21] is shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…4. While only the overall transition intensity was adjusted to fit the data for the 548-keV E2 transition, the mixing ratios were also varied to fit the correlations for the mixed were also in agreement with those measured and are similar to those published for la4W in [13]. A partial level scheme of 197Au which incorporates several firm spin assignments determined in our related study [20,21] is shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…While the extraction of the relative gyromagnetic ratios of levels in 197Au from the simultaneously measured TF precessions is rather straightforward [12][13][14]22], to obtain absolute g-factors of states in 197Au from the observed precession angles requires knowledge of the behaviour (velocity-dependent magnitude) of the TF for Au ions recoiling through the particular ferromagnetic host. In earlier publications [5,6,8] we discussed the abrupt discontinuity in TF strength which occurs between 76Os and 7sPt ions traversing polarized Fe hosts with velocities ~ 0.02 c. In contrast with TF studies using Fe hosts, no discontinuities [20,21].…”
Section: Transient Field Calibration and G-factors Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[23, 24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43]. One caveat on this statement is that S(θ γ ) is a very sensitive function of θ γ when the detectors are placed near the maximum slope of the angular correlation as is done for precession measurements.…”
Section: Transient-field Impacmentioning
confidence: 99%